2015
DOI: 10.5194/acp-15-9917-2015
|View full text |Cite
|
Sign up to set email alerts
|

Meteor radar quasi 2-day wave observations over 10 years at Collm (51.3° N, 13.0° E)

Abstract: Abstract. The quasi 2-day wave (QTDW) at 82-97 km altitude over Collm (51 • N, 13 • E) has been observed using a VHF meteor radar. The long-term mean amplitudes calculated using data between September 2004 and August 2014 show a strong summer maximum and a much weaker winter maximum. In summer, the meridional amplitude is slightly larger than the zonal one with about 15 m s −1 at 91 km height. Phase differences are slightly greater than 90 • on an average. The periods of the summer QTDW vary between 43 and 52 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 41 publications
3
31
0
Order By: Relevance
“…The few previous studies either focused on the thermosphere/ionosphere, where the wave amplitudes are dominated by the temperature dependence of dissipative processes in the E‐region and tidal‐planetary wave interactions to imprint the planetary wave periods on this altitude regime (e.g., Forbes et al, 2018; Koval et al, 2018), or long‐term radar observations in the mesosphere. The former do not matter for the current question, and the latter are largely focused on the quasi‐2‐day wave (Q2DW) ranging from no correlation at northern midlatitudes (Lilienthal & Jacobi, 2015), to large positive correlation in the meridional wind but negative correlation with the zonal wind at subtropical NH latitudes (Gu et al, 2013), to small negative correlations at the equator (Rao et al, 2017). Moudden and Forbes (2014) found a positive Q2DW correlation with the solar cycle in SABER temperatures in the SH and no correlation in the NH, in contrast to Huang et al (2013) who reported a positive correlation in the SH and NH.…”
Section: Discussionmentioning
confidence: 99%
“…The few previous studies either focused on the thermosphere/ionosphere, where the wave amplitudes are dominated by the temperature dependence of dissipative processes in the E‐region and tidal‐planetary wave interactions to imprint the planetary wave periods on this altitude regime (e.g., Forbes et al, 2018; Koval et al, 2018), or long‐term radar observations in the mesosphere. The former do not matter for the current question, and the latter are largely focused on the quasi‐2‐day wave (Q2DW) ranging from no correlation at northern midlatitudes (Lilienthal & Jacobi, 2015), to large positive correlation in the meridional wind but negative correlation with the zonal wind at subtropical NH latitudes (Gu et al, 2013), to small negative correlations at the equator (Rao et al, 2017). Moudden and Forbes (2014) found a positive Q2DW correlation with the solar cycle in SABER temperatures in the SH and no correlation in the NH, in contrast to Huang et al (2013) who reported a positive correlation in the SH and NH.…”
Section: Discussionmentioning
confidence: 99%
“…McCormack et al () found that the QTDW may be forcing in both the tropical and extratropical regions related to baroclinic/barotropic instability during the sudden stratospheric warming (SSW). Lilienthal and Jacobi () found that summer QTDW in the mesosphere is amplified after a maximum of zonal wind shear. Combining the two mechanisms, QTDWs may be a near‐resonant mode excited by baroclinic instability.…”
Section: Introductionmentioning
confidence: 99%
“…The quasi-two day wave (QTDW) is one of the dominant features in the mesosphere and lower thermosphere typically maximizing after the solstices. There are many observation reports on QTDW by radars (Gu, Li, Dou, Wang, et al, 2013;Harris & Vincent, 1993;Lilienthal & Jacobi, 2015;Ma et al, 2017;Meek et al, 1996;Muller, 1972;Nozawa et al, 2003;Pancheva, 2006) and satellites (Gu, Li, Dou, Wu, et al, 2013;Lieberman, 1999;Rodgers & Prata, 1981;Wu et al, 1993). The observed dominant QTDWs are mainly westward propagating with zonal wave numbers 3 (W3) and 4 (W4), which are strong in the Southern Hemisphere (SH) and Northern Hemisphere (NH), respectively (Gu, Li, Dou, Wu, et al, 2013;Tunbridge et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The 16 year horizontal wind observations from medium‐frequency radar show that the QTDW in January also tends to peak at ~48 h [ Gu et al , ]. In addition, it was also found that the periods of the QTDW in boreal summer are more distributed and variable ranging from ~40 to 60 h [ Harris , ; Gu et al , ; Lilienthal and Jacobi , ]. Nevertheless, the reasons for the variability of the QTDW period are not clear yet.…”
Section: Introductionmentioning
confidence: 99%